Psychopedagogical support of higher education students in Belgium within the framework of the discipline "Integration activities related to higher education - AILES" - Souza, Joiciane Aparecida de (2019)
The psychopedagogical support carried out within the framework of the discipline "integration activities related to higher education - AILES" at the High School Francisco Ferrer of Brussels, in Belgium, aims at helping the students to: 1. build their professional projects, 2. carry out relevant literature searches, 3. find the most appropriate working methods for them, and 4. clearly define the expectations of higher education towards students and the adaptation to this new context. I aim to offer a caring and specialized support, taking into account the cognitive, emotional, metacognitive and social dimensions of the student. I also try to develop reflective thinking and student confidence in their own learning abilities.